2020
DOI: 10.7717/peerj-cs.298
|View full text |Cite
|
Sign up to set email alerts
|

Managing slow-moving item: a zero-inflated truncated normal approach for modeling demand

Abstract: This paper proposes a slow-moving management method for a system using of intermittent demand per unit time and lead time demand of items in service enterprise inventory models. Our method uses zero-inflated truncated normal statistical distribution, which makes it possible to model intermittent demand per unit time using mixed statistical distribution. We conducted numerical experiments based on an algorithm used to forecast intermittent demand over fixed lead time to show that our proposed distributions impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The current packages available in the software [ 28 ] allow us to work with distributions belonging to the GAMLSS family. The models can be selected according to goodness-of-fit criteria when fitting real-world data, as well as by generating random numbers with arbitrary distributions of interest for theoretical or empirical research [ 12 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current packages available in the software [ 28 ] allow us to work with distributions belonging to the GAMLSS family. The models can be selected according to goodness-of-fit criteria when fitting real-world data, as well as by generating random numbers with arbitrary distributions of interest for theoretical or empirical research [ 12 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The computational routines were implemented in a non-commercial software named in its version 4.0.3. For more details of this software, see (accessed on 16 July 2021), and, for packages related to inventory models, see [ 30 , 33 , 34 , 35 , 36 ]. The computer specifications used in these experimental results are reported in Table 3 .…”
Section: Simulation Study and Real Pharmaceutical Case Studymentioning
confidence: 99%
“…We implemented our proposal in a non-commercial software named R; see http://www.r-project.org . See Rojas, Leiva, Wanke, and Marchant (2015) , Rojas, Wanke, Coluccio, Vega-Vargas, and Huerta-Canepa ( 2020 ), Wanke, Ewbank, Leiva, and Rojas (2016) and Wanke and Leiva (2015) to visualize R applications in supply models .…”
Section: Methodsmentioning
confidence: 99%
“…In non-DL models, Jang [8] showed that travel demand follows a zero-inflated negative binomial distribution. Rojas et al [28] also noted that using a zero-inflation model is promising for modeling intermittent travel demand. However, recent demand prediction papers sidestepped this challenge by choosing a low resolution, such as 60 minutes [11,12].…”
Section: Uncertainty Of Sparse Travel Demand Predictionmentioning
confidence: 99%
“…We assume that the inputs follow the ZINB distribution [9,28]. A random variable that follows NB distribution has a probability mass function 𝑓 𝑁 𝐵 as:…”
Section: Zero-inflated Negative Binomial (Zinb) Distributionmentioning
confidence: 99%